2020
DOI: 10.5114/aoms.2019.89407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of risk factors between colon cancer and rectum cancer in a single medical center hospital, Taiwan

Abstract: Introduction: Colorectal cancer (CRC) is rapidly increasing in developed countries. In Taiwan, the incidence rate of CRC has increased during the past decade, but the 5-year survival has remained at approximately 63%. In this study, we sought to determine the 5-year survival rate of patients diagnosed with colon and rectum cancer and to determine factors affecting survival. Material and methods: All patients from the Taiwan Cancer Database of the medical center hospital in North Taiwan between 2007 and 2013 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Furthermore, we showed that hospitalization for AECOPD within 1 year before surgical resection was an independent prognostic factor for survival in patients receiving standard treatments for stage I–III colon adenocarcinoma; patients with more frequent hospitalizations for AECOPD (≥2 within 1 year before surgical resection) before colon adenocarcinoma treatments had poorer survival outcomes than did those with less frequent AECOPD hospitalizations before colon adenocarcinoma treatments. In addition, our study results are compatible with those of previous studies, which have identified age, comorbidity, cigarette smoking status, histological differentiation, perineural invasion, lymphovascular invasion, and AJCC pathologic stages as independent predictors of OS [ 26 , 27 , 28 , 29 , 30 ]. The present study is the first to identify hospitalization frequency for AECOPD before colon adenocarcinoma treatments as a severity-dependent independent prognostic factor for the OS of patients with stage I–III colon cancer receiving surgical resection and standard treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we showed that hospitalization for AECOPD within 1 year before surgical resection was an independent prognostic factor for survival in patients receiving standard treatments for stage I–III colon adenocarcinoma; patients with more frequent hospitalizations for AECOPD (≥2 within 1 year before surgical resection) before colon adenocarcinoma treatments had poorer survival outcomes than did those with less frequent AECOPD hospitalizations before colon adenocarcinoma treatments. In addition, our study results are compatible with those of previous studies, which have identified age, comorbidity, cigarette smoking status, histological differentiation, perineural invasion, lymphovascular invasion, and AJCC pathologic stages as independent predictors of OS [ 26 , 27 , 28 , 29 , 30 ]. The present study is the first to identify hospitalization frequency for AECOPD before colon adenocarcinoma treatments as a severity-dependent independent prognostic factor for the OS of patients with stage I–III colon cancer receiving surgical resection and standard treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Studies show that the 5-year survival rate of individuals with COAD is 65% in the United States, with 5-year survival rate of stage I and II COAD patients ranging from 80 to 90%, whereas that of patients with stage III and IV metastatic diseases being 60–71 and 8–13%, respectively. Further, Fang et al have reported 5-year survival rates of 74.3% for stage I, 76.6% for stage II, 56.6% for stage III, and only 16.7% for stage IV ( 2 , 3 ). Accordingly, early and timely diagnosis and treatment of colon cancer are very important for favorable patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The multivariate analysis also showed that high EGFR intensity increases the risk of cancer recurrence 4.3 times (HR = 4.3). Interestingly, our study showed that among patients with high EGFR levels, patients with pT4 predominated (p = 0.0003), although some researchers claim that the correlation between the EGFR overexpression and clinical-pathological parameters is not important [2,23,24,25]. According to them, this may be only an additional molecular phenomenon that causes poor test results.…”
Section: Outcomementioning
confidence: 68%